2008
DOI: 10.1177/0969733008092868
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Care for Patients With HIV/AIDS

Abstract: This study aims to describe and compare nurses' willingness to provide care for patients with HIV/AIDS and factors associated with this in three countries. An international cross-sectional survey was conducted among nurses working in medical, surgical and gynaecology units in Finland (n =427), Estonia (n =221) and Lithuania ( n =185) in early 2006. The response rates were 75% (n = 322) in Finland, 54% (n =119) in Estonia and 86% (n = 160) in Lithuania. A modified version of a scale developed in 1994 by Dubbert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
(19 reference statements)
2
11
0
1
Order By: Relevance
“…Du trečdaliai visų ŽIV, infekuotų žmonių gyvena į pietus nuo Sacharos Afrikoje. Per pastaruosius dvejus metus žmonių, gyvenančių su ŽIV skaičius padidėjo [16]. ŽIV infekcijos mastai nemažėja ir Baltijos jūros regione: 2010 metais Suomijoje buvo apie 2200, Estijoje daugiau nei 5000 ir Lietuvoje 3300 žmonių, gyvenančių su ŽIV ir/ar AIDS.…”
unclassified
“…Du trečdaliai visų ŽIV, infekuotų žmonių gyvena į pietus nuo Sacharos Afrikoje. Per pastaruosius dvejus metus žmonių, gyvenančių su ŽIV skaičius padidėjo [16]. ŽIV infekcijos mastai nemažėja ir Baltijos jūros regione: 2010 metais Suomijoje buvo apie 2200, Estijoje daugiau nei 5000 ir Lietuvoje 3300 žmonių, gyvenančių su ŽIV ir/ar AIDS.…”
unclassified
“…The lack of knowledge concerns not only hygiene routines, but also the meaning and possible consequences of antibiotic resistance. 9,[18][19][20][21] Previous studies have examined the experiences of staff caring for patients with other antibiotic-resistant bacteria besides ESBL and other infectious diseases. Patients in isolation receive fewer visits from staff because of the effort required to don protective clothing for every visit.…”
mentioning
confidence: 99%
“…They may fear that if they become infected, they could lose their job and thus their income. 11,[21][22][23][24][25][26] In a study of HIV, Suominen et al 27 reported that fear could result in staff choosing to avoid caring for these patients. Increasing the level of staff knowledge has been shown to reduce fear, and to increase the readiness of staff to care for patients with infectious diseases.…”
mentioning
confidence: 99%
“…Välimäki et al (2008) conducted a study that compared the willingness of nurses to provide care to PLWHIV in three different countries: Finland, Lithuania, and Estonia. In this study, they identified that of the three countries the Estonian nurses were the least willing to provide care to PLWHIV.…”
Section: A Poisoned Relationship: Plwhiv and Healthcare Providersmentioning
confidence: 99%
“…This is very interesting because in 2010, Välimäki et al conducted another study comparing the willingness of nursing and midwifery students to provide services for PLWHIV in Estonia, Finland, and Lithuania. This study identified that the majority of Estonian nursing and midwife students, 84% of whom were under the age of 24, were willing to provide the same services to PLWHIV asked of nurses in the Välimäki et al (2008) study (Välimäki et al, 2010). Although the locations of the study in Estonia was not clarified, the difference in attitudes between the Estonian participants in these two studies supports the findings of this study that HIV stigma is primarily associated with people 25 years old and older, and that members of the younger generations are not as concerned with HIV as those of the older generations.…”
Section: A Poisoned Relationship: Plwhiv and Healthcare Providersmentioning
confidence: 99%